PEMBAHARUAN PENDIDIKAN ISLAM DI MINANGKABAU ABDUL KARIM AMRULLAH DAN ABDULLAH AHMAD - Rahimma, Wisma; Handika, Tata (As-Sulthan Journal of Education, 2024)
Abdul Karim Amrullah and Abdullah Ahmad are reformers of Islamic education in Minangkabau. These two figures played an important role in the advancement of Islamic education in Minangkabau. The purpose of this article is to find out the thoughts on Islamic education and the concept of Islamic education initiated by Abdul Karim Amrullah and Abdullah Ahmad and how the differences and similarities in the thoughts of Islamic education from Abdul Karim Amrullah and Abdullah Ahmad. This research is a descriptive qualitative research with library research method. The results of this study indicate that Abdul Karim Amrullah carried out educational reforms in the curriculum field, namely incorporating religious sciences and languages ​​into the Islamic education curriculum reaching twelve subjects and using various kinds of books. These subjects are Nahwu Science, Sharaf Science, Fiqh Science, Interpretation Science, Monotheism Science, Hadith Science, Musthalah Hadith Science, Mantiq Science, Ma'ani Science, Bayan Science, Ushul Fiqh Science, the learning method used by Abdul Karim Amrullah is by changing the education system from halaqah to classical, while Abdullah Ahmad carried out educational reforms in the curriculum sector, namely integrating the curriculum of religious education and general education, and learning methods, namely debating clubs, reward and punishment methods and methods of playing games and recreation.